8=8(c-87)

Simple and best practice solution for 8=8(c-87) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8=8(c-87) equation:



8=8(c-87)
We move all terms to the left:
8-(8(c-87))=0
We calculate terms in parentheses: -(8(c-87)), so:
8(c-87)
We multiply parentheses
8c-696
Back to the equation:
-(8c-696)
We get rid of parentheses
-8c+696+8=0
We add all the numbers together, and all the variables
-8c+704=0
We move all terms containing c to the left, all other terms to the right
-8c=-704
c=-704/-8
c=+88

See similar equations:

| 15=7+4c | | 3a(4a-5)+7=3 | | 82-x=(1/4)2x | | -8=n/4-10 | | 2(x–2/3)=0 | | -8=n4-10 | | 1/2x-19=11x= | | x/4+13=21 | | (6x+7)(5x^2+4x=7) | | 44=-3b-1 | | -15=-12x+21 | | (-6w-1)(-5w-8)=0 | | 54.4=n-3 | | 9x+15=2x+20+2x | | 2a-6=30a= | | y=-2/3(0)+10=10 | | Y=11x+400 | | 8x-14=180+2x+10=180 | | 8x-14+2x+10=180 | | x/2+3=x+4 | | (3-6x)/3=7x-2 | | -6/7v=42 | | 3y–12=3 | | 7x–3=6x–13 | | t−6t+10=−5−3t | | 4f+7=4f+5 | | 6.1=32x-2.9x+2.5 | | 0.05x+0.03(35000–x)=1250 | | −3d+7=7−3d | | n+35=40* | | 19v+4v+13=−20+20v | | 10p+5=-8+10p |

Equations solver categories